THE INFLUENCE OF CONCEPT ATTAINMENT MODEL IN MATHEMATICAL COMMUNICATION ABILITY AT THE UNIVERSITY STUDENTS - Lilis Marina Angraini (IKIP Siliwangi and I-MES, 2019)
Based on data from observation and interview with lecturer who teaches mathematics course on the subject under study, it was found that students' mathematical communication ability is still low. This study aims the students’ mathematical communication ability through Concept Attainment Model learning. The method in this study is two groups randomized subject post-test only. The number of subjects in this study were 82 students. The Kolmogorov-Smirnov test, Levene test, t test, ANOVA one and two-way were used to analyse the data. The results of this study showed that (1) there is difference grade on the student’s mathematical communication ability between experimental group and conventional group as a whole, (2) there is no difference on the students’ mathematical communication ability of experimental classes based on their Prior mathematical knowledge (PMK); (3) there is no interaction between the learning that is used with the students’ prior mathematical knowledge on the students’ mathematical communication ability. The concept attainment model provides a better influence on students’ mathematical communication ability, it is also necessary to see the influence of the concept attainment model on students' high-level mathematical thinking ability.